2022
DOI: 10.1093/jncimonographs/lgac021
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Geriatric Assessment Measures into National Cancer Institute Clinical Trials

Abstract: To improve the care of older adults with cancer, the traditional approach to clinical trial design needs to be reconsidered. Older adults are underrepresented in clinical trials with limited or no information on geriatric-specific factors, such as cognition or comorbidities. To address this knowledge gap and increase relevance of therapeutic clinical trial results to the real-life population, integration of aspects relevant to older adults is needed in oncology clinical trials. Geriatric assessment (GA) is a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…Globally, the number of older persons aged 65 years and over is projected to increase [ 1 ]. People aged 65 years and over have been frequently excluded from research (e.g., clinical trials); when included, researchers often do not report analysis by age [ 48 , 49 ]. Our review was not specific to gender, sex, ethnicity, or frailty [ 46 ].…”
Section: Methodsmentioning
confidence: 99%
“…Globally, the number of older persons aged 65 years and over is projected to increase [ 1 ]. People aged 65 years and over have been frequently excluded from research (e.g., clinical trials); when included, researchers often do not report analysis by age [ 48 , 49 ]. Our review was not specific to gender, sex, ethnicity, or frailty [ 46 ].…”
Section: Methodsmentioning
confidence: 99%
“…Perhaps there are better times in the course of disease-times of recurrence or when a therapeutic change is considered or after toxicity-that would also be important. 76 Additionally, the strongest evidence supporting the use of GA and GAM is not fully representative of those who most often get cancer. The accrual of older adults into clinical trials remains well below their representation as patients with cancer.…”
Section: Gaps In the Literature And Future Research Directionsmentioning
confidence: 99%
“…Perhaps there are better times in the course of disease—times of recurrence or when a therapeutic change is considered or after toxicity—that would also be important. 76…”
Section: Gaps In the Literature And Future Research Directionsmentioning
confidence: 99%
“…For example, one recent study demonstrated that sarcopenia was associated with an increased risk of ICANS and longer length of hospital stay. 83 Consistently gathering additional data (including geriatric assessment) 84,85 about the baseline health of individuals enrolled in clinical trials of CAR T-cell and BsAbs will improve clinicians' insight into whether their patients are similar to those treated on trial and identify those who may be at increased risk for toxicity, allowing more informed shared decision making.…”
Section: Access To Care and Equity In Real-world Settingsmentioning
confidence: 99%